Comprehensive DFT study of 3-(2-furyl)-1 H-pyrazole-5-carboxylic acid: structural, spectroscopic, and electronic properties with optoelectronic implications - Yilmaz, Mucahit (Nature Portfolio, 2025)
In this study, the structural and electronic properties of the compound 3-(2-furyl)-1 H-pyrazole-5-carboxylic acid have been theoretically investigated by Density Functional Theory (DFT). The most stable geometry of the molecule was optimized and vibrational frequencies were calculated at the B3LYP/6-31G(d) level. Geometry optimization results indicate that the molecule adopts a planar conformation, meaning all constituent atoms lie within the same geometrical plane. This confirms that the atomic arrangement is not spatially random or dispersed in three dimensions, but instead exhibits a well-defined two-dimensional planar geometry. In addition to geometric optimization, quantum chemical calculations show that the molecule has high electronic stability and low reactivity, and also reveal its potential for optoelectronic applications with strong absorption properties in the UV. These analyses contribute to the structural confirmation of the compound and provide important information on the chemical reactivity of the functional sites. The results obtained show that the compound has significant potential for optoelectronic, pharmaceutical and sensor applications.
Keywords: 3-(2-furyl)-1H-pyrazole-5-carboxylic acid; Quantum chemical calculations; DFT; MEP; NMR; FT-IR